A geography of Brazil in 3 dimensions - Moriconi-Ebrard, Francois [UNESP] (Revues Org, 2019)
The relative importance of these three phases is measured using three simple variables: the central geocoordinates of the municipalities, the evolution of their population since 1872, under the constraint of the elevation above the sea level variable. This model allows to reconstruct by a theoritical reasoning the fundamental characteristics of the spatial structures of Brazil. It opposes among other things two societies : that of Littoral / Nordeste to that of the heights of the Interior, which is a political reality still current. This modeling also makes it possible to reconnect certain human and physical basic realities which found the unity of the geographical sciences.
Keywords: Spatial modelization; Brazil; Population; Geohistory; Topography